Restrictions on the Export of Medical Products Hamper Efforts to Contain Coronavirus Disease (COVID-19) in Latin America and the Caribbean - Economic Commission for Latin America; the Caribbean (United Nations, 2020)
Latin America and the Caribbean is highly dependent on imports of medical products, as less than 4% of these are sourced within the region itself. To date, more than 70 countries —including four of the region’s top five suppliers, of which the first is the United States— have restricted their medical exports in response to COVID-19. Export restrictions are hampering the supply of products essential for fighting the pandemic in the region. Latin America and the Caribbean should make it a strategic objective to strengthen its productive capabilities in the pharmaceutical and medical supplies and equipment industries, in order to gain a less vulnerable footing to face health crises in the future. This will require the combined efforts of the public sector, business and academia in a mission-oriented industrial policy framework. Several of the region’s countries have made worthwhile efforts in that direction, which must be sustained beyond the current pandemic.